Az új Btk. időbeli hatálya az egyes általános részi rendelkezések tükrében - Antal, Zsófia (Debreceni Jogi Műhely, 2017)
Act of 2012 on the Criminal Code came into force on the 1st of July 2013 after a long codification period.  A new Criminal Code always leads to problems in application of law, therefore, it is quite actual to make an examination on new provisions. Some classic provisions of the General Part remained the same, although the penalty system and some other regulations have been renewed. The temporal scope of the new code will possibly be in focus for years.The aim of this research is to take an examination on the case law and judicial decisions of Hungarian courts related to temporal scope of the new Criminal Code that is a significant part of this paper. The new Hungarian Criminal Code has been required to be prepared more severe than the former code. The other aim of this research is to revise the new provisions of the General Part resulting in statements about whether these new rules are more severe or more lenient than the Act IV of 1978.For this purpose a close legal interpretation shall be taken into account.